Fabrication of durable self-repairing superhydrophobic fabrics via a fluorinate-free waterborne biomimetic silicification strategy. (5th March 2019) - Sun, Yihan; Huang, Jinxia; Zhao, Siyang; Guo, Zhiguang
Abstract : A water-based methodology integrating an in situ biomimetic silicification and fluorinate-free modification strategy for preparing self-repairing superhydrophobic fabrics is presented. Abstract : Herein, a simple, facile and versatile protocol was presented to fabricate water-resistant fabrics based on an in situ bio-silicification strategy and fluorinate-free modification. The whole fabrication procedure is green and avoids the need for any fluorinate-containing compounds, environmentally harmful organic solvents and high preparation temperature. The produced fabrics maintained robust lyophobic properties after multiple machine laundry cycles, repeated abrasion cycles, UV irradiation, and organic solvent and strong acid/base attacks. The obtained superhydrophobic fabrics exhibited repeatable self-repairing behaviour against repeated washing and oxygen plasma etching cycles. Our in situ biomimetic silicification strategy for developing robust self-repairing superhydrophobic fabrics using a waterborne fluorinate-free coating system well fits the motifs of green chemistry and will lead to the development of green preparation of other superwetting surfaces.